2021
DOI: 10.18632/aging.203207
|View full text |Cite
|
Sign up to set email alerts
|

Circ_0081001 down-regulates miR-494-3p to enhance BACH1 expression and promotes osteosarcoma progression

Abstract: The study was aimed at deciphering the function and mechanism of circ_0081001 in osteosarcoma (OS). In this study, quantitative real-time polymerase chain reaction (qRT-PCR) was utilized for quantifying circ_0081001, miR-494-3p, and BTB domain and CNC homolog 1 (BACH1) mRNA expressions in OS tissues and cells. Cell counting kit-8 (CCK-8) assay, together with 5-Ethynyl-2'-deoxyuridine (EdU) assay, was performed for evaluating cell proliferation; the alterations in apoptosis were analyzed utilizing flow cytometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
2
7
0
Order By: Relevance
“…Moreover, the function of hsa-miR-494 as a tumor inhibitor restricts the proliferation and development of OS. The observably decreased hsa-miR-494-3p was also observed in OS specimens by previous studies [25,26]. In our work, hsa-miR-494 expression was appreciably suppressed in OS Computational and Mathematical Methods in Medicine compared with control group, and OS patients with downregulated hsa-miR-494 have a worse prognosis, indicating that our results are consistent with the consequences of previous investigations.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the function of hsa-miR-494 as a tumor inhibitor restricts the proliferation and development of OS. The observably decreased hsa-miR-494-3p was also observed in OS specimens by previous studies [25,26]. In our work, hsa-miR-494 expression was appreciably suppressed in OS Computational and Mathematical Methods in Medicine compared with control group, and OS patients with downregulated hsa-miR-494 have a worse prognosis, indicating that our results are consistent with the consequences of previous investigations.…”
Section: Discussionsupporting
confidence: 92%
“…Deficiency of circDNA2 down-regulated CCDC6 level and suppressed the proliferative capacities of GC cells by sponging miR-149-5p [34] . Hsa_circ_0081001 (circCYP51A1) is found as an oncogenic factor in OS [35] . Another study reported that circ_0081001 contributed to methotrexate sensitivity through the regulation of miR-494-3p/transglutaminase 2 pathway [36] .…”
Section: Discussionmentioning
confidence: 99%
“…e miR-494-3p is upregulated in endometrial cancer, glioma, retinoblastoma, and hepatocellular carcinoma, which promotes cancer progression by regulating the PTEN/PI3K/AKT pathway [33][34][35][36]. While miR-494-3p is downregulated in synovial sarcoma, prostate cancer, osteosarcoma, and oral squamous cell carcinoma, and acts as a tumor suppressor miRNA [37][38][39][40]. Furthermore, miR-494-3p was associated with a new tumor driver of lung cancer.…”
Section: Discussionmentioning
confidence: 99%